Project management factors affecting the enterprise resource planning projects’ performance in Jordan - Abu-Hussein, Ruba; Hyassat, Mohammed; Sweis, Rateb; Alawneh, Afnan; Al-Debei, Mutaz (Journal of systems and information technology, 2016)
Purpose This purpose of this research is to investigate the project management factors that are affecting the enterprise resource planning (ERP) projects’ performance in Jordan. Based on the conducted literature review, four project management areas were selected for this research: the communication management, the human resource management, the time management and the risk management. Design/methodology/approach In total, 24 Jordanian ERP projects were surveyed through designing a questionnaire that was distributed to project managers. Moreover, interviews were conducted with both the project manager of the largest ERP project in Jordan and a consultant of one of the Big 5 consulting firms. Findings The interviews’ results confirmed the effect of the four project management areas on the ERP project performance which is consistent with the questionnaire results except for the risk management. Originality/value No similar studies were found in Jordan. Moreover, this subject was tackled by only a few studies, so more research is recommended to investigate the project management factors that are affecting the ERP projects’ performance. It is also recommended that future studies extend this research on factors other than project management factors.